The Influence Of Digital Leadership, Knowledge Management Capability, And Strategic Networking On The Business Strategic Agility Of Technology Startup Companies - Wylda Olivia Kowey; Anita Bawaiqki Wandanaya; Joice Siahaya; Anthoneta Telsy Waelauruw; Leonora Ferdinandus; Heppi Syofya (Indonesian Journal of Innovation Multidisipliner Research, 2026)
The purpose of this research is to describe how Digital Leadership, Knowledge Management Capabilities and Strategic Networking impact Business Strategic Agility of Technology Start-Up Companies. A quantitative methodology was used, including survey data collected from the completed questionnaires of two hundred employees and managers who work in Technology Start-Up Companies, selected through purposive sampling. The selection criteria were that each respondent had to be an employee of the company for a minimum of one year, be an active participant in development and / or operational activities within the company, and must use digital technology in their daily activities. Data were analysed using multiple linear regression; validity and reliability testing were carried out as well as normality, heteroscedasticity and multicollinearity were tested for classical assumptions. The findings revealed that Digital Leadership, Knowledge Management Capability, and Strategic Networking have both partially and simultaneously a significant and positive impact on Business Strategic Agility. In order to improve Business Strategic Agility, organizations can enhance Digital Leadership skills, develop Knowledge Management Capabilities, and create stronger Strategic Networks. The purpose of this research is to assist in developing adaptive and competitive business strategies for technology startups.